MANAJEMEN PENGEMBANGAN KEGIATAN BELAJAR MELALUI KECERDASAN KINESTETIK - akbar muhibuddin, fachri (PT. Solusi Komunikasi Terapan, 2023)
The title was made in this study about management development learning activities through the kinesthetic intelligence against the background of the problem based on the application curriculum of the 2013 demand the liveliness of the learners in the learning process, because physical motion turned out to have major contributions as revealed based on venon magnesen research say that brain of the human quick to get information from visual modality moving. Learning by doing must be a priority, because student learns 20% by reading, 30% by listening, 40% by looking, 50% by speaking, 60% by doing and 90% by looking, speaking and doing. The goal for obtaining an overview of the steps of planning, implementation, brominated and solutions in developing management development learning activities through the kinesthetic intelligence. Then was able to muster an effective category learning activities as well as efficient or can we take apart that learning it the right grind and grind it correctly. While the research conducted using qualitative methods descriptive observational field as well as supporting documentation. As for the results of the research obtained by the researchers are learning activities through the kinesthetic intelligence methods actually build a very productive learning atmosphere, during the development of the visible learning activities learning well and learners are very enthusiastic for the contribute in learning activities. Then it can be inferred that learning must have a principle of motion, change and evolve, kinesthetic intelligence help the whole body more responsive learning activities, class as a learning space should be one place of learning, and the teacher is able to realize the needs of every learner in the learning. Problems encountered based on explanation of the findings above, it is likely to be passive learners when learning activities are less than creative categories. The recommendations could be given for teachers on request able to conceptualize the active learning activities